Predictors of Colorectal Cancer Screening and Screening Modalities among Patients seen at Federally Qualified Health Centers Funded by the United States Health Resources and Services Administration - Megan R.M. Aaronson; Nadereh Pourat; Connie Lu; Jayraan Badiee; Helen Yu-Lefler; Benjamin Picillo; Hank Hoang; Folasade P. May (Preventive Medicine Reports)
Introduction: Federally qualified health centers provide primary care services to millions of low-income patients in the United States who face challenges accessing colorectal cancer (CRC) screening. We aimed to understand how patient-level factors influence CRC screening participation and screening modality choice in this setting. Methods: We examined data from the 2022 Health Center Patient Survey, 2021 Uniform Data System, and Area Health Resource File. We performed generalized multilevel logistic regression and multinomial regression to measure associations between our independent variables and receipt of any CRC screening and of screening modalities. Results: Among 1584 patients ages 50–75, most (56 %) reported having CRC screening, including 33 % with endoscopic screening only, 16 % with stool-based screening only, and 7 % with multiple modalities. Selected factors associated with any CRC screening included having five or more health center visits in the past year (aOR = 1.66, 95 %CI = 1.07–2.56), being insured (Medicaid aOR = 2.25, 95 %CI = 1.44–3.54; other insurance aOR = 2.69, 95 %CI = 1.51–4.82), living within 30  minutes of the health center (aOR = 1.93, 95 %CI = 1.15–3.25), having multiple comorbidities (aOR = 1.72, 95 %CI = 1.13–2.63), using telehealth (aOR = 1.52, 95 %CI = 1.02–2.27), and having a flu shot last year (aOR = 1.77, 95 %CI = 1.29–2.45). We observed that patients who are non-Hispanic Black (aOR = 3.52, 95 %CI = 1.28–9.68) and who do not speak English well or at all (aOR = 5.54, 95 %CI = 1.64–18.75) reported having multiple modalities. Conclusion: Federally qualified health center patients reported endoscopic CRC screening more commonly than stool-based screening, and barriers to access such as distance to the health center and English proficiency were impactful. Increasing CRC screening in low-income populations requires improving access and promoting opportunities for less invasive screening.